ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, DAN DANA ALOKASI UMUM TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL DI KOTA BANDUNG - Muhammad Anzhal Al Haqi Chaniago; Ririt Iriani (Economic Education, University of Jember, 2023)
With the enactment of a decentralized system, local governments have the authority to regulate government affairs in their own regions. Therefore, fiscal decentralization policy is accompanied by regional autonomy policy as a step to increase financial capacity and implementation of regional autonomy carried out by regional governments. The management of regional financial potential will have large regional financial resources to develop the region further. This study aims to see the effect of Economic Growth, local revenue (PAD), General Allocation Fund (DAU) on Capital Expenditure in Bandung City in 2010-2022. The type of research used in this study is a quantitative approach, which describes causality between variables by testing existing data hypotheses according to their usefulness. In this study, there is time series data, namely 2010-2022 using Bandung City data. Descriptive statistical methods carried out in this research analysis include classical assumption tests, regression analysis, and hypothesis tests, including coefficients of determination and t tests, using Eviews 10 software. The results of the study showed no significant effect of economic growth and local revenue on capital expenditure. Meanwhile, general allocation funds have a significant influence on capital expenditure.